Free market ideology and deregulation in Colorado's oil fields: Evidence for triple movement activism?. Issue 3 (4th May 2017) - Malin, Stephanie A.; Mayer, Adam; Shreeve, Kelly; Olson-Hazboun, Shawn K.; Adgate, John
ABSTRACT: Unconventional oil and gas extraction (UOGE) has spurred an unprecedented boom in onshore production in the US. Despite a surge in related research, a void exists regarding inquiries into policy outcomes and perceptions. To address this, support for federal regulatory exemptions for UOGE is examined using survey data collected in 2015 from two Northern Colorado communities. Current regulatory exemptions for UOGE can be understood as components of broader societal processes of neoliberalization. Free market ideology increases public support for federal regulatory exemptions for UOGE. Perceived negative impacts do not necessarily drive people to support increased federal regulation. Utilizing neo-Polanyian theory, interaction between free market ideology and perceived negative impacts is explored. Free market ideology appears to moderate people's views of regulation: increasing the effect of perceived negative impacts while simultaneously increasing support for de regulation. To conclude, the ways in which free market ideology might normalize the impacts of UOGE activity are discussed.